Pomegranate Juice Supplementation Alters Utero-Placental Vascular Function and Fetal Growth in the eNOS−/− Mouse Model of Fetal Growth Restriction - Finn-Sell, Sarah L.; Cottrell, Elizabeth C.; Greenwood, Susan L.; Dilworth, Mark R.; Cowley, Elizabeth J.; Sibley, Colin P.; Wareing, Mark (Frontiers in Physiology, 2018)
The eNOS-/- mouse provides a well-characterized model of fetal growth restriction (FGR) with altered uterine and umbilical artery function and reduced utero- and feto-placental blood flow. Pomegranate juice (PJ), which is rich in antioxidants and bioactive polyphenols, has been posited as a beneficial dietary supplement to promote cardiovascular health. We hypothesized that maternal supplementation with PJ will improve uterine and umbilical artery function and thereby enhance fetal growth in the eNOS-/- mouse model of FGR. Wild type (WT, C57Bl/6J) and eNOS-/- mice were supplemented from E12.5-18.5 with either PJ in their drinking water or water alone. At E18.5 uterine (UtA) and umbilical (UmbA) arteries were isolated for study of vascular function, fetuses and placentas were weighed and fetal biometric measurements taken. PJ supplementation significantly increased UtA basal tone (both genotypes) and enhanced phenylephrine-induced contraction in eNOS-/- but not WT mice. Conversely PJ significantly reduced UtA relaxation in response to both acetylcholine (Ach) and sodium nitroprusside (SNP), endothelium dependent and independent vasodilators respectively from WT but not eNOS-/- mice. UmbA sensitivity to U46619-mediated contraction was increased by PJ supplementation in WT mice; PJ enhanced contraction and relaxation of UmbA to Ach and SNP respectively in both genotypes. Contrary to our hypothesis, the changes in artery function induced by PJ were not associated with an increase in fetal weight. However, PJ supplementation reduced litter size and fetal abdominal and head circumference in both genotypes. Collectively the data do not support maternal PJ supplementation as a safe or effective treatment for FGR.